2013
DOI: 10.7454/mst.v16i2.1510
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Thermal Properties of Polypropylene Reinforced by Calcined and Uncalcined Zeolite

Abstract: This study was carried out to compare mechanical and thermal properties of polypropylene (PP) reinforced with uncalcined and calcined zeolites. The PP samples were reinforced with zeolites at various quantities of 2, 4, and 6 (wt %). The comparison of the two types of zeolite was based on mechanical properties, including tensile strength, elongation at break, and Young's modulus, and thermal characteristics analyzed using DSC, and DTA/TGA technique. The results obtained clearly revealed that both zeolites were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Based on the results, the membrane with 1% nanozeolite loading had improved tensile strength when compared to the pure PSf sample. According to Bukit, N. (2012), it was explained that the well dispersion of nanozeolite to the polypropylene matrix allowed the nanocomposite membrane to carry more tensile load due to the formation of strong interfacial layer between the reinforced nanomaterial and the material [10]. This phenomenon was also observed in another study conducted by Liang et al, (2000) where they added the glass beads as fillers in the polypropylene matrix, thus, the interfacial layer created absorbed certain amount of stress from the matrix to the filler during the deformation [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results, the membrane with 1% nanozeolite loading had improved tensile strength when compared to the pure PSf sample. According to Bukit, N. (2012), it was explained that the well dispersion of nanozeolite to the polypropylene matrix allowed the nanocomposite membrane to carry more tensile load due to the formation of strong interfacial layer between the reinforced nanomaterial and the material [10]. This phenomenon was also observed in another study conducted by Liang et al, (2000) where they added the glass beads as fillers in the polypropylene matrix, thus, the interfacial layer created absorbed certain amount of stress from the matrix to the filler during the deformation [11].…”
Section: Resultsmentioning
confidence: 99%
“…Another interesting characteristic of this compound is its ability to capture carbon dioxide (CO2) gas, which is why zeolites are also used as adsorbent material in the separation of CO2 gas from air [9]. Nanozeolites can also enhance the mechanical property of a polymer as in the case where Nurdin Bukit (2012) observed that the addition of zeolite in polypropylene matrix had enhanced the tensile strength of the composite material [10].…”
Section: Introductionmentioning
confidence: 99%
“…Peningkatan terbesar untuk kekuatan tarik pada komposisi 8 dan 10 %berat nano ASP tanpa kompatibiliser. Penambahan komposisi nano abu sekam padi dapat mengurangi dispersibeality abu sekam padi yang bisa dikaitkan dengan interaksi bahan pengisi dari ASP yang tinggi dapat menghasilkan aglomerat (penggumpalan), sehingga interkalasi dari matrik HDPE yang meleleh menjadi interlayer ASP menjadi lebih sulit dan menyebabkan kekuatan tarik dan tegangan yield menurun, demikian juga halnya dengan hasil penelitian [16,17].…”
Section: Hasil Karakterisasi X-ray Diffractometry (Xrd)unclassified
“…The sample was subjected to calcination treatment at 600 °C for 2 hours, and then grinded for 10 hours using planetary ball mill PBM 4. After this treatment, the calcined zeolite was found to have the particle size of 190.2 nm [18]. Analyses XRF in Table 3 XRD analysis of natural zeolite obtained by purification and calcination phase containing major mineral type mordenite (CaAl 2 Si 10 O 24 .7 H 2 O).…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, modification of zeolite to increase its surface hydrophobicity is required to promote the compatibility of zeolite and organic polymers. The most common modification methods applied are thermal treatment at temperature of 600-1100 °C [17][18][19] and chemical modification using strong acids or strong bases [20][21]. In this study, natural zeolite was modified by calcination at 600 °C to activate the zeolite while retaining its amorphous state [17].…”
Section: Introductionmentioning
confidence: 99%